DEVELOPMENT OF RELIGIOUS CURRICULUM FOR WOMEN'S TAKLIM COUNCIL - Zamakhsyari, Neng Ikrimah Aziz; Kattani, Abdul Hayyie Al; Rosyadi, A. Rahmat (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Majelis taklim is a non-formal educational institution that has a strategic role in improving the religious quality of the community, especially women. Unfortunately, many taklim assemblies still hold learning activities without a structured curriculum guide that is in accordance with the needs of the congregation. This causes learning materials to be often not on target, less systematic, and unable to answer the challenges of religious and social life faced by worshippers. Therefore, it is necessary to develop a religious curriculum based on the real needs of female worshippers so that the learning process becomes more directed, effective, and meaningful. This research uses the research and development method using the ADDIE (Analysis, Design, Develop, Implement and Evaluate) model. The analysis stage is carried out with two analyses, namely needs analysis and product analysis. In the integrated design stage with the Tyler model, a model religious curriculum for the women's taklim assembly was designed which resulted in an initial prototype design. In the development stage, expert validation of the initial prototype consisted of curriculum development experts, material experts and linguists so that a second prototype was produced. At the implementation stage, validation was carried out by practitioners of the second prototype. At the evaluation stage, improvements were made to the third prototype based on assessments and suggestions from previous experts so that the final product was produced. The results of the study show that the main needs of pilgrims include understanding of the knowledge of the Qur'an, faith, women's jurisprudence (including worship, munakahat, muamalah, and funeral arrangements), morals-Sufism, family education, and health. The curriculum is designed with components: objectives, materials, methods, and learning evaluations that are structured systematically and contextually. The validation results show that the curriculum is very feasible to use. This curriculum can be a reference for the organizers of the taklim assembly in organizing religious education in accordance with the needs and characteristics of adult female worshippers